How Interdisciplinarians Work - Woodill, Sharon; Plate, Richard; Jagoda, Nathan (Journal of Interdisciplinary Studies in Education, 2019)
Interdisciplinary research requires an approach different from research performed within a specific disciplinary framework. This paper reports on a study that was motivated by a perceived difference between how interdisciplinary research is done by scholars and how it is taught to students. A total of 21 semi-structured interviews were conducted with professional scholars who had presented at one of the Association for Interdisciplinary Studies recent annual conferences with the objective of exploring how professional scholars approach and perform interdisciplinary research. Three themes that arose from these interviews—1) the importance of an exploratory disposition, 2) a lack of concern for interdisciplinary boundaries, and 3) the importance of mentorship and community—have relevance in terms of how we design curriculum and educational experiences to prepare students to research complex, real-world problems that require an interdisciplinary approach.